A dimensão educativa no trabalho dos agentes comunitários de saúde do Programa de Saúde da Família - Zinn, Gabriela Rodrigues (2007)
The present study object is the health education in the practical work of the Communitarian Agents of Health (Agentes Comunitários de Saúde - ACS), the objective was to investigate the educative practical developed by the ACS from the Family Health Program (Programa de Saúde da Família - PSF) of a Health Centers (Unidade Básica de Saúde - UBS) in the North Zone periphery, in São Paulo City. The relevance of this research is justified, predominantly, by the affirmation of the binomial education and health, existing in a dialectic relation. In the context of the Brazilian Public Health, the PSF shows a strategy with approach in the health promotion using a essential instrument that is the health education for all the families. The ACS is the professional of the PSF that has more frequent contact and proximity with the population, ahead of this, it becomes pertinent to investigate which are educative practices used for these professionals in order to deepen the scientific knowledge of this reality and, thus, to put it in a context and to identify possible strategies and boardings, difficulties and easinesses presents in this interaction. A descriptive and explorative research of qualitative matrix was carried through using assisted observation associated to interviews. As theoretical bedding there is the dialogical and emancipated education, and the health-illness process understood as resultant of the decurrent strengthen and consuming factors of the different forms of insertion in the society with its different forms to work and to live. There was identified four categories presents in the educative practical developed by the ACS : (a) the Communitarian Agent of Health work; (b) the relation between the Communitarian Agent of Health and the population; (c) the functioning dynamics of the Health Service and (d) the Communitarian Agent of Health as educator; these categories contemplate subcategories and they send us to the reflection about the educative potential presented by the ACS that contemplates attributes of proximity and affectivity in the relation with the population, but that still assumes one reiterate practice of the present ideologies although the existence of reflective moments which do not find structural endorsement for a educative practical change with sights for a transforming performance